Policy Evaluation on Food Safety Regulation: Study Case on Risk Management Program on Food Safety in Indonesia - Akhmad Fahmi Hikmatiyar; Yudo Anggoro (Journal of International Conference Proceedings (JICP), 2021)
In 2015, the Indonesian FDA issued Head of Indonesian FDA Regulation Number 14 of 2015 revised by Head of Indonesia FDA number 2 of 2017 then Head of Indonesia FDA number 21 of 2019 concerning the Implementation of the Risk Management Program (RMP) on Food Safety in Food Industry. This regulation mandatory requires foodstuff intended for particular nutritional uses (such as milk formula) and low acid can food industry in Indonesia to implement a risk-based food safety self-regulatory control system. This study aims to identify parameters of costs, problems, challenges, and benefits in implementing and operating RMP as a policy evaluation in the perspective of economic aspect. The result showed cost parameters that were considered important in the implementation of RMP, including documenting system, costs related to staff training, the cost for investment in new technology and equipment, and external consultant. While the benefit parameters that are expected by the industry in implementing RMP include the fast-track scheme optimization which is a special benefit from RMP, RMP branding to the public, and lifting obligation for HACCP certification for foodstuff intended for particular nutritional uses industry. These parameters are expected to be the basis for policymakers to improve the implementation of RMP.